2020
DOI: 10.3390/cancers12113371
|View full text |Cite
|
Sign up to set email alerts
|

Promising Therapy in Lung Cancer: Spotlight on Aurora Kinases

Abstract: Despite tremendous efforts to improve the treatment of lung cancer, prognosis still remains poor; hence, the search for efficacious therapeutic option remains a prime concern in lung cancer research. Cell cycle regulation including mitosis has emerged as an important target for cancer management. Novel pharmacological agents blocking the activities of regulatory molecules that control the functional aspects of mitosis such as Aurora kinases are now being investigated. The Aurora kinases, Aurora-A (AURKA), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 76 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…Accordingly, the AURKs, in particular AURKA and B were proposed as promising targets for cancer therapy, e.g. in lung cancer treatment ( Galetta and Cortes-Dericks, 2020 ), where AURK inhibition is currently evaluated in clinical trials. In view of recent findings, indicating therapeutic benefit of combined inhibition of IGF2BP1-RNA binding by BTYNB and the CDK4/6 inhibitor palbociclib, the identification of conserved upregulation of AURKA by IGF2BP1 suggests that IGF2BP1 inhibition may improve AURKA-inhibition in combined therapies ( Müller et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the AURKs, in particular AURKA and B were proposed as promising targets for cancer therapy, e.g. in lung cancer treatment ( Galetta and Cortes-Dericks, 2020 ), where AURK inhibition is currently evaluated in clinical trials. In view of recent findings, indicating therapeutic benefit of combined inhibition of IGF2BP1-RNA binding by BTYNB and the CDK4/6 inhibitor palbociclib, the identification of conserved upregulation of AURKA by IGF2BP1 suggests that IGF2BP1 inhibition may improve AURKA-inhibition in combined therapies ( Müller et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of small molecule inhibitors to target AURKs have been developed and are in different phases of clinical trials. The development of AURKA inhibitors and their progress has been described recently [ 7 ]. The possibility of targeting AURKB has gained momentum during last few years.…”
Section: Targeting Aurkb In Cancermentioning
confidence: 99%
“…Overexpression of AURKs in tumors has been shown to trigger aneuploidy and genomic instability [ 6 ] that leads to tumor development, invasion and metastasis. AURKA and its functions have been widely investigated and several reviews were authored to highlight its importance in cancer [ 7 , 8 ]. The role of AURKC in cancer is not completely understood and needs further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Although Mibefradil was proved to have therapy effect in several tumor types, such as leukemia [41] and glioblastoma [42], its anti-tumor pharmacologic mechanism was never elucidated clearly. In this study, through target prediction and molecular docking, we found AURKA, a serine or threonine kinase [43,44], was the therapy target for Mibefradil in TNBC. Mibefradil treatment could inhibit the expression and phosphorylation of AURKA, which finally led to apoptosis enhancement in TNBC.…”
Section: Discussionmentioning
confidence: 87%